Analyzing Social Disorders in Structured Orders:An Introduction to the ASRI Model - Ovie-D'Leone, Alex Igho (American Journal of Humanities and Social Sciences, 2018)
There exists a nexus between environmental variables and defects in human psychologies acting as trajectories for conflict outbreaks in human societies. Models of conflict resolutions abound in this area but are majorly applicable in culture specific regions. Since conflicts are universally and naturally occurring social phenomena, the paper argues for and introduces an ASRI model which constitutes a universalist frame of analysis that attempts to capture all ranges of possible dysfunctional variables likely to become complicit in conflict outbreaks: 'A' for the ACTOR factors, 'S' for the social stractification formulas for social ordering, 'R' for the manners of evolving the operating rules, and ' I' the manners of evolving the operating Institutions. This frame effectively captures the synergies existing between environmental variables and human agency variables trapped usually in a normal conflict causation.